Simulated ischaemia/reperfusion impairs trophoblast function through divergent oxidative stress- and MMP-9-dependent mechanisms - Barron, Aaron; Tuulari, Jetro; Karlsson, Linnea; Karlsson, Hasse; O'Keeffe, Gerard W; McCarthy, Cathal M (Portland Press Ltd., 2025)
Early-onset pre-eclampsia is believed to arise from defective placentation in the 1st trimester, leading to placental ischaemia/reperfusion (I/R) and oxidative stress. However, our current understanding of the effects of I/R and oxidative stress on trophoblast function is ambiguous in part due to studies exposing trophoblasts to hypoxia instead of I/R, and which report conflicting results. Here we present a model of simulated ischaemia/reperfusion (SI/R) to recapitulate the pathophysiological events of early-onset PE, by exposing 1st trimester cytotrophoblast HTR-8/SVneo cells to a simulated ischaemia buffer followed by reperfusion. We examined different ischaemia and reperfusion times and observed that 1h ischaemia and 24h reperfusion induced an increase in reactive oxygen species (ROS) production (p < 0.0001) and oxygen consumption rate (p < 0.01). SI/R-exposed trophoblast cells exhibited deficits in migration, proliferation and invasion (p < 0.01). While the deficits in migration and proliferation were rescued by antioxidants, suggesting a ROS-dependent mechanism, the loss of invasion was not affected by antioxidants, which suggests a divergent ROS-independent pathway. In line with this, we observed a decrease in MMP-9, the key regulatory enzyme necessary for trophoblast invasion (p < 0.01), which was similarly unaffected by antioxidants, and pharmacological inhibition of MMP-9 replicated the phenotype of deficient invasion (p < 0.01). Collectively, these data demonstrate that I/R impairs trophoblast migration and proliferation via a ROS-dependent mechanism, and invasion via a ROS-independent loss of MMP-9, disambiguating the role of oxidative stress and providing insights into the response of trophoblasts to I/R in the context of early-onset PE.